The Future Prospects of the Evolution of Islamic Law Thought from the Classical to the Contemporary Era - Muhammadong, Muhammadong; khaerunnisa , Khaerunnisa (PT. Anagata Sembagi Education, 2025)
The growth of Islamic legal philosophy from the classical to the present era illustrates the rapid transformations in the social, political, and intellectual situations within the Muslim community. This study is based on the evolution of Islamic legal philosophy, transitioning from rigid interpretations of classical texts to more adaptable and contextual methodologies in the contemporary period. This research seeks to examine the future possibilities of Islamic legal thought by elucidating the elements that are catalyzing these transformations and its ramifications for the application of Islamic law in the modern context. The methodology utilized is qualitative, using literature analysis that includes both classical and contemporary materials, alongside the concepts of distinguished Islamic legal thinkers. The findings indicate that, notwithstanding difficulties in upholding the authority of traditional Islamic law, there exists considerable potential for the evolution of a more inclusive and adaptable Islamic legal framework to confront modern concerns. The study emphasizes the significance of discussion between classic and contemporary experts in influencing the future of Islamic legal philosophy.